2016
DOI: 10.1177/0001839216657311
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Political Embeddedness in China

Abstract: Economic transitions in countries that move from state planning and redistribution to market exchange create business opportunities but also uncertainty, because many interdependent factors-modes of exchange, types of products, and forms of organizations-are in flux. Uncertainty is even greater when the country's political institutions remain authoritarian because the rule of law is weak and state bureaucrats retain power over the economy. This study of listed firms in China, which has recently seen economic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
264
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(269 citation statements)
references
References 103 publications
4
264
0
1
Order By: Relevance
“…To address this issue, we used the propensity score matching (PSM) method, which is commonly used in management research on firms' social networks (Choi et al 2014, Haveman et al 2016. Propensity score matching alleviates endogeneity concerns by matching firms receiving treatment (obtaining political connection) or not on the observable variables, and thus eliminating spurious results caused by these variables (Dehejia and Wahba 2002, Rosenbaum andRubin 1983).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…To address this issue, we used the propensity score matching (PSM) method, which is commonly used in management research on firms' social networks (Choi et al 2014, Haveman et al 2016. Propensity score matching alleviates endogeneity concerns by matching firms receiving treatment (obtaining political connection) or not on the observable variables, and thus eliminating spurious results caused by these variables (Dehejia and Wahba 2002, Rosenbaum andRubin 1983).…”
Section: Estimation Methodsmentioning
confidence: 99%
“…Unlike Whited and Wu (2006), we do not include a dividend-paying indicator in the function because this study explicitly studies dividend policy. Instead, we include a state ownership indicator, considering that SOEs in China have an inherent advantage in receiving external finance (Qian, 1994;Kornai, 1998;Tian, 2005;Jia et al, 2013;Chen, 2015;Haveman et al, 2016). For instance, Chen (2015) also confirms privilege of state-controlled enterprises to access equity financing.…”
mentioning
confidence: 99%
“…Baker's study () of relationships between investment banks and corporations found support for a power interpretation of networks by showing how resource dependence structures who transacts with whom. Among listed firms in China, political embeddedness has been shown to improve firm performance by increasing access to bank loans and assuaging the interests of controlling shareholders (Haveman, Jia, Shi, & Wang, ). Ties to powerful firms may not always have positive effects.…”
Section: Network Analysis and The Problem Of Embeddednessmentioning
confidence: 99%